RANCANG BANGUN PERBANDINGAN LUAS BATERAI BERBAHAN ALUMINIUM MENGGUNAKAN ELEKTROLIT AIR LAUT BERSIRKULASI TERBUKA DENGAN SISTEM KONTROL DATA TERSIMPAN - Gilbert Mario Sembiring; Juan Evan Soaduon Tampubolon; Agus Dharma; I Gusti Agung Putu Raka Agung; I Made Mataram (Program Studi Teknik Elektro UNUD, 2025)
The utilization of renewable energy in Indonesia remains suboptimal, despite its substantial potential. One promising approach to harness this potential is through aluminum-air batteries using seawater as an electrolyte, offering greater safety and sustainability compared to conventional batteries. However, the performance of aluminum-air batteries can still be improved, particularly in terms of stabilizing the no-load voltage. This study aims to determine the voltage output generated by two battery design methods with identical electrode surface areas: one configuration using four cells measuring 5 × 5 × 0.2 cm arranged in series, and the other using a single cell measuring 10 × 10 × 0.2 cm. Both designs operate with an open circulation system. For testing, both battery configurations were monitored using an Arduino microcontroller as a voltage reader, which captured the voltage output from each battery. The voltage output from the aluminum-air batteries was read by the Arduino through the ADC pin and displayed in real time on a 16x2 I2C LCD screen, with the seawater circulation driven by a DC pump acting as the flow medium. The experimental results showed that the aluminum-air battery with four cells of 5 × 5 × 0.2 cm arranged in series achieved a maximum voltage increase of 255.7%, reaching 4.34 V, compared to the single-cell configuration of 10 × 10 × 0.2 cm, which produced only 1.22 V.